The Effect of Intellectual Capital Investment, Corporate Governance, and Barriers to Entry on the Intellectual Capital Performance of Banking Companies - Rosanda Asmara Hakiki; Erida Herlina (Universitas Hayam Wuruk Perbanas, 2021)
Intellectual capital is an important element in determining the performance of banking companies. This study aimed to examine the effect of intellectual capital investment, good corporate governance (proxied by foreign ownership and institutional ownership), and barriers to entry on intellectual capital performance. This research was conducted on conventional banking companies listed on the Indonesia Stock Exchange from 2015 to 2019. The sample was selected using a purposive sampling method based on specific criteria. Eighty-nine banking companies met the criteria. Data analysis was performed using multiple linear regression analysis. The results of this study indicate that intellectual capital investment and barriers to entry have a negative effect on intellectual capital performance. On the other hand, foreign ownership and institutional ownership have no significant effect on intellectual capital performance. These findings recommend that banking companies pay attention to efficiency in investment in human resource development to improve bank performance. Inefficient investment in human resources can lead to a decrease in intellectual capital performance. Banking companies also need to continuously innovate service products to maintain their competitiveness and noÂ longer rely on fixed asset investment as an element of a barrier to entry.